Analisis Dampak Tren Budaya K-Pop Terhadap Gaya Hidup Mahasiswa Fakultas Ilmu Sosial Universitas Islam Negeri Sumatera Utara Medan - Erwan Efendi; Azrin Eka Putra; Qari Ananda Azhari Hasibuan (EduInovasi: Journal of Basic Educational Studies, 2025)
The purpose of this research is to find out how the impact of the K-pop trend on the lifestyle of students of the Faculty of Social Sciences, State Islamic University of North Sumatra Medan. This research is a field study with a descriptive qualitative approach. The data source of this research is divided into two first, primary data where the research data is obtained from the results of interviews with students of the Faculty of Social Sciences UINSU directly in the field. Second, secondary data is data obtained from journal documents and previous research. The results showed that K-Pop cultural trends have a significant impact on the lifestyle of students of the Faculty of Social Sciences UINSU Medan. This influence can be seen in their consumption behavior, way of dressing, social activities, and outlook on life. K-Pop culture is not just entertainment, but also a part of the students' identity and lifestyle. The lifestyle changes that occur reflect the shifting values and preferences of students, who are increasingly influenced by global popular culture. While these lifestyle changes can be considered a legitimate form of self-expression, it is important for individuals to maintain a balance between following trends and maintaining their values and cultural identity, so as not to lose their way in finding their identity as a student.